Experimental study on mechanical properties of fiber reinforced concrete: Effect of cellulose fiber, polyvinyl alcohol fiber and polyolefin fiber. (20th November 2020) - Xu, Haiyan; Shao, Zimeng; Wang, Zhijie; Cai, Libin; Li, Zhen; Jin, Hesong; Chen, Tiewei
Highlights: Cellulose fiber is found to enhance axial compressive strength of concrete but weakens splitting tensile strength. Polyvinyl alcohol fiber weakens axial compressive strength, splitting tensile strength and shear strength of concrete. High dosage of fiber may lead to ineffective interweaving and agglomeration. 1.5 kg/m 3 Cellulose fiber with 1.0 kg/m 3 polyvinyl alcohol fiber is found to be optimal combination to achieve the best synergistic effect. Abstract: Mechanical properties of concrete reinforced with cellulose fiber (CTF), polyvinyl alcohol fiber (PF) and polyolefin fiber suitable for various spray (VS) are experimentally studied. The individual impact of single fiber as well as synergistic effect of hybrid fiber on axial compressive strength, splitting tensile strength and shear strength of concrete are investigated. Microstructures of fiber reinforced concrete specimen as well as its stress–strain relationship is also observed. The results show that CTF alone enhances axial compressive strength of concrete but weakens splitting tensile strength; VS weakens splitting tensile strength as well but has little impact on the other two strength; PF has a negative effect on all the three mechanical strength. Synergistic effect of hybrid fiber varies with dosage, and only with the appropriate fiber dosage can hybrid fiber has positive synergistic effect on mechanical properties. 1.5 kg/m 3 cellulose fiber with 1.0 kg/m 3 polyvinyl alcohol fiber is found to be optimal combination of CTF-PF hybrid fiber to achieve the best synergistic effect. Practical implications of CTF, PF and VS are also put forward.